Review of Understanding The Concept of Solution Acid and Bases Level Macrosciopic and Microcospic Class XI SMA Negeri 1 Batu - Wicaksono, Ardian Trio (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2016)
This research is descriptive. The population in this study is the student 'SMA Negeri 1 Batu, while the study sample represented students randomly by class XI IPA 3 SMA Negeri 1 Batu 2011/2012 school year. Type of instruments used in the form of a written test in the form of an objective with five alternative answers. Technique of data collecting is done through two phases: preparation and implementation stage. From the results of research conducted a few conclusions obtained are: (1) Understanding the concept of acid and alkaline solution student 'SMA Negeri 1 Batu at the macroscopic level are classified as good by 84% the percentage of comprehension, (2) Understanding the concept of acid and alkaline solution of XI class students SMA Negeri 1 Batu IPA at the microscopic level considered adequate by 64% the percentage of comprehension, and (3) There is a relationship between students' understanding of the concept of macroscopic with microscopic students' understanding of concepts in a solution of acid and base material because rhitung ≥ rtabel.